Determinants of local food purchase Insight from a consumer survey in South Tyrol (Italy) - Brozzi, Riccardo; Stawinoga, Agnieszka; Hoffmann, Christian; Streifeneder, Thomas (Socio.hu Társadalomtudományi Szemle, 2016)
A large number of previous studies relate local food purchase to the demographic and financial profile of consumers. This article provides an innovative insight into the sociocultural and spatial factors influencing local food purchase in the multilingual region of South Tyrol (Italy). To derive a representative sample for the South Tyrolean population, 498 consumers have been interviewed through Computer Assisted Telephone Interviewing (CATI). The differences in the consumer attitudes towards local food were tested for significance using both parametric and non–parametric statistical tests. The results show that consumers’ cultural background and spatial typology (according to their urban, predominantly urban and rural place of residence) have a significant influence on specific attitudes towards local food purchase. More specifically, differences in urban/rural consumers are observable with regard to the preferred stores to purchase at and in the level of expenditure on local food. The cultural background influences the meanings associated with local food and the reasons attributed to its purchase. Key words: local food, attitudes, rural urban relations, regional development